Analisis Ekonomi Usahatani Padi Sawah di Kecamatan Basala (Studi Kasus Desa Lipumasagena) - Nurul Asma; Muh Yani Balaka; Tadjuddin Tadjuddin (Universitas Halu Oleo, 2019)
This study aims to determine the factors that significantly influence the production of rice farmers in Lipu Masagene Village. This study uses a quantitative approach with a total sample of 60 families. Analysis of the data used in this study is the analysis of Multiple Linear Regression, where the variables are Labor (X1), Land area (X2), Capital (X3) and Expertise (X4) and Rice Production (Y).The results of this study indicate that the land area, labor, capital and expertise simultaneously significantly influence the increase in rice production in Lipumasagena Village. The area of land and while labor has a significant effect on increasing rice productions, capital, and expertise have no significant effect on increasing rice production